An Averaging Principle for Hilfer Fractional Stochastic Evolution Equations with Non-Instantaneous Impulses - Beibei Li; Junyan Bao; Peiguang Wang (Fractal and Fractional, 2025)
This paper investigates non-instantaneous impulsive Hilfer fractional stochastic evolution equations. To obtain a more accurate convergence rate, an equivalent form of the above equation is derived by the time-scale separation method. Then, we prove that the solution of the equivalent equation converges to that of the averaged equation. Furthermore, we estimate the convergence rate between the exact and approximate solutions of the equation. Finally, we provide an example to justify our result.